Trastorno de ansiedad debido a enfermedad médica y cambio emocionales en paciente con insuficiencia renal - Litardo Gomez, Juan Pablo (2019)
The present study is about a psychological clinical case carried out in the Dial-Rios Hemodialysis Unit of the Babahoyo canton, province of Los Ríos. This clinical case was done to a 49-year-old patient named Maria (fictitious name), who has a medical condition called chronic renal failure (CRF) and emotional changes caused by the disease and its treatment in said patient. Here a psychological interview was carried out on the patient and her closest relative in this case, her husband, after this she proceeded to fill out her medical history, in addition to the execution of an observation sheet, not forgetting her position, the importance of taking a psychological test, which in this case was the Hamilton anxiety scale test. Once all the necessary information was gathered based on the psychological tools used, a diagnostic approach was achieved, which is described in the following pages of this text, also in this case study psychotherapeutic techniques were carried out that gave way to a psychotherapeutic scheme in the cognitive-behavioral approach, this being the proposal for the solution of said case